Terapi Kotrimoksazol pada Ensefalitis Toxoplasma dengan Penyakit AIDS: Laporan Kasus - Dwi Arshanti, Tyas; Dewi, Putri Purnama (Cermin Dunia Kedokteran, 2026)
Introduction: Toxoplasma encephalitis (TE) is the most common opportunistic infection affecting the central nervous system in patients with HIV/ AIDS and is associated with high morbidity and mortality. In individuals with HIV, TE tends to be more severe and life-threatening. The first-line therapy for TE is a combination of pyrimethamine and sulfadiazine; however, the limited availability of these drugs in some healthcare settings makes cotrimoxazole a potential alternative to pyrimethamine. Case: A 50-year-old Balinese male, married, was brought to the emergency department with confusion lasting for two days prior to admission. Two weeks earlier, he had experienced headache, weakness, odynophagia, and weight loss of 8 kg within one month. The patient had a history of multiple sexual partners, frequent consumption of raw lawar, and occupational exposure as a pig farm worker. Physical examination revealed white plaques on the tongue and pharynx. Laboratory investigations showed a reactive HIV rapid test with a CD4 count of 11 cells/μL, positive anti-Toxoplasma gondii IgG antibodies, and contrast-enhanced cranial CT scan demonstrating multifocal ring-enhancing lesions in the right and left parietal regions with associated cerebral edema. The patient was diagnosed with stage IV HIV/AIDS, oropharyngeal candidiasis, and toxoplasma encephalitis, and was treated with cotrimoxazole 960 mg every 8 hours. Clinical improvement was observed after 11 days of treatment, and follow-up contrast-enhanced CT scan on day 18 showed radiological improvement with reduced perifocal edema and decreased number of lesions. Discussion: The diagnosis of toxoplasma encephalitis in patients with HIV/AIDS is established based on a combination of clinical manifestations, serological findings, and characteristic radiological features. In situations where pyrimethamine and sulfadiazine are unavailable, cotrimoxazole may serve as an effective alternative therapy. The favorable clinical and radiological responses observed in this case support the use of cotrimoxazole as an alternative treatment option for toxoplasma encephalitis. Conclusion: Cotrimoxazole may serve as an effective alternative therapy for toxoplasma encephalitis in patients with reactive HIV infection, particularly in settings where first-line therapy is unavailable, with favorable clinical and radiological outcomes.